The Value of Human Life in the Demand for Safety: Extension and Reply - Conley, Bryan C. (American Economic Review, 1978)
Both Philip Cook and Michael Jones-Lee criticize my assumption that the critical value above which the value of human life (VHL) exceeds is presumably at a level of reply, I develop an extension the original article, which eliminates this qualification, and reconstruct my in light of their comments. line with common usage, I had defined as expected discounted lifetime labor income (p. 47) without any subtraction of necessary expenditures as would be required in determining business income. However, such expenditures must be so subtracted properly define a meaningful income. As a leading accounting text emphasizes: In computing the (available dividends) a period all forms of expense incurred in the of such must be provided for (Eldon Hendriksen, p. 62). Put another way, all of business is a surplus and may be taxed or distributed without any loss of output (in the short run). The public finance literature has similarly recognized that should be deducted from [gross] income, regarding such outlays as a cost of production (Richard Musgrave, p. 171), and Adam Smith admonished that taxable should be defined as 'clear' income, or as above subsistence (Musgrave, p. 95). To define accurately, one must therefore subtract from gross receipts a level of expenditure which allows continued work and makes the individual indifferent between life and death. Only gross receipts above this level are potentially taxable or available safety expenditures. If a major share of gross receipts is taxed leaving funds less than (as measured by amount CO in Figure 2 of the original paper), the person will starve death, otherwise perish, or commit suicide. Thus any useful definition of net consistent with its inherent meaning as a measure of surplus must subtract from some measure of gross the expenditures necessary living. The same holds consumption. However, is difficult measure and possibly highly variable among individuals. I expect it is on average at a low level of income, as argued below. Given this change, my results are valid under all circumstances. That is, if C' = C CO and Y' = Y Y?, VHL > C'(= Y') in all cases. Graphically, the slope of the tangent any point on a curve, as shown in Figure 2, will always be less than the ray arising out of CO the intercept value on U. We have found that VHL = f(UIC')l (OU/OC')j * C', and the factor in brackets is the inverse of a'. Since it is also the slope of the ray divided by the tangent, from the previous line of reasoning, the quotient is always greater than one, a' is always less than one and the value of human life is always greater than consumption (where consumption and are defined of expenditures). Cook wishes to provide a relatively transparent derivation of Conley's major theoretical result, which avoids the complexity of his multiperiod model (p. 710). A simple of the main results is contained in my original footnote 16.' His last sentence is a reasonable caveat my origi-